Previous Malignancy as a Risk Factor for the Second Solid Cancer in a Cohort of Nuclear Workers - Mikhail Osipov; Mikhail Sokolnikov (Ital Publication, 2021)
This paper describes the results of epidemiological analysis of a cohort of nuclear workers hired at the main facilities of "Mayak" Production Association located in the city of Ozyorsk in Southern Urals of the Russian Federation. Previous malignancy as a risk factor for second cancer in a cohort of 22,373 workers occupationally exposed to ionizing radiation has been analyzed in a retrospective study with more than 60 years of follow-up. Information on main radiation and non-radiation risk factors (attained age, sex, tobacco smoking), as well as the dose of exposure to occupational ionizing radiation has been obtained for the analysis using the data from cancer register as well as other main population registries created in Epidemiological Laboratory of Southern Urals Biophysics Institute. Poisson's regression realized in the "Amfit" module of "Epicure" statistical package has been applied for risk analysis. Excess relative risk per 1 Gy of absorbed dose of external gamma radiation and internal alpha radiation has been calculated using linear model. Among the 2,471 cancer cases accumulated in the study cohort to the end of follow-up 6.4% of second cancer cases have been diagnosed among workers occupationally exposed to protracted external gamma- and internal alpha radiation. The relative risk of second cancer (except for non-melanoma skin cancer) among nuclear workers with previously diagnosed cancer was about 4 times higher after a decade compared with those cancer patients who had single cancer only. The results showed that previous malignancy along with main non-radiation factors is statistically significant carcinogenic risk factor among nuclear workers exposed to protracted occupational radiation.   Doi: 10.28991/SciMedJ-2021-0301-2 Full Text: PDF